THE BEHAVIOR OF α-ELEMENTS ABUNDANCES IN THE THIN AND THICK DISKS OF THE GALAXY - Mishenina, T. V.; Gorbaneva, T. I.; Soubiran, C.; Bienayme, O.; Kovtyukh, V. V.; Korotin, S. A. (Одеські астрономічні публікації, 2017)
We have carried out the detailed analysis of 350 high-resolution spectra of FGK dwarfs and giants. Abundances of Fe, Si, Ca and Ni have been determined under LTE approximation, whereas abundances of Mg have been determined under NLTE approximation. Spatial velocities with an accuracy better than 1 km/s-1, as well as orbits, have been computed for dwarfs (or all) stars. They have been used to define 2 subsamples kinematically representative of the thin disk and the thick disk in order to highlight their respective properties. A transition occurs at [Fe/H] = -0.3. Stars more metal-rich than this value have a flat distribution with Zmax<1 kpc and σW<20 km/s-1, and a narrow distribution of [α/Fe]. There exist stars in this metallicity regime which cannot belong to the thin disk because of their excentric orbits, neither to the thick disk because of their low scale height. Several thin disk stars are identified down to [Fe/H] = - 0.80. Their Mg enrichment is lower than thick disk stars with the same metallicity. Both the dwarfs and the giants show a decrease of [α/Fe] with [Fe/H] in the thick disk.